Pengaruh Pelatihan dan Kompensasi Terhadap Kinerja Pegawai Dinas Pemberdayaan Perempuan Perlindungan Anak dan Keluarga Berencana Kabupaten Waropen - Rosita Riski Rahayu; Agoeng Karyanto; Dedi Hidayat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of training and compensation on employee performance at the Women's Empowerment, Child Protection, and Family Planning Office of Waropen Regency, and to identify variables that have a dominant influence. The focus of the study is directed at efforts to improve employee performance through measurable and targeted human resource development strategies. This study uses a quantitative descriptive method with data collection techniques through field observation, questionnaire distribution, and document review. The study population includes all 39 employees of the office, with a census sampling technique so that all members of the population are respondents. The research instrument was tested for validity and reliability, while data analysis was carried out using multiple linear regression tests and t-tests using the SPSS version 23 program for Windows. The test results show that training has a significant effect on employee performance, with a significance value of 0.011 and a calculated t of 2.678 > t table 2.02269. Furthermore, compensation also has a significant effect on employee performance, with a significance value of 0.009 and a calculated t of 2.755 > t table 2.02269. Beta coefficient analysis shows that compensation has the most dominant influence on employee performance, with a Standardized Coefficient Beta value of 0.440. This finding indicates that improving training quality and providing adequate compensation can contribute significantly to employee performance in local government agencies. Planned, task-relevant training accompanied by fair compensation will motivate employees to perform optimally. Based on the research results, it is recommended that management strengthen competency-based training programs and review the compensation system to better align with employee contributions. This is expected to serve as a policy basis for efforts to improve performance and achieve organizational goals sustainably.